Wireless Back‐haul: a software defined network enabled wireless Back‐haul network architecture for future 5G networks. Issue 6 (1st November 2015) - Niephaus, Christian; Aliu, Osianoh Glenn; Kretschmer, Mathias; Hadzic, Senka; Ghinea, Gheorghita
Abstract : Recently both academic and industry worlds have started to define the successor of long term evolution, so‐called 5G networks, which will most likely appear by the end of the decade. It is widely accepted that those 5G networks will have to deal with significantly more challenging requirements in terms of provided bandwidth, latency and supported services. This will lead to not only modifications in the access segment and parts of core networks, but will trigger changes throughout the whole network, including the Back‐haul segment. In this work the authors present their vision of a 5G Back‐haul network and identify the associated challenges. They then describe their wireless Back‐haul architecture, which implements software defined network concepts and further extends them into the wireless domain. Finally the authors present a brief overview of their evaluation results.